2023
DOI: 10.3390/nu15122675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Animal and Vegetable Proteins on Gut Microbiota in Subjects with Overweight or Obesity

Abstract: The gut microbiota plays a pivotal role in the balance between host health and obesity. The composition of the gut microbiota can be influenced by external factors, among which diet plays a key role. As the source of dietary protein is important to achieve weight loss and gut microbiota modulation, in the literature there is increasing evidence to suggest consuming more plant proteins than animal proteins. In this review, a literature search of clinical trials published until February 2023 was conducted to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…Thus, the food we eat shapes the GM's structure, function, and composition and, eventually, the healthy aging process [43]. Primarily 'animal-based' or 'plant-based' diets lead to significant alterations in the gut microbiota in humans [44,45]. The GM ferments undigested dietary fibers, producing short-chain fatty acids that play crucial roles in enterocyte differentiation, growth arrest, and apoptosis.…”
Section: Dietary Interventions For Modulation Of Gut Microbiotamentioning
confidence: 99%
“…Thus, the food we eat shapes the GM's structure, function, and composition and, eventually, the healthy aging process [43]. Primarily 'animal-based' or 'plant-based' diets lead to significant alterations in the gut microbiota in humans [44,45]. The GM ferments undigested dietary fibers, producing short-chain fatty acids that play crucial roles in enterocyte differentiation, growth arrest, and apoptosis.…”
Section: Dietary Interventions For Modulation Of Gut Microbiotamentioning
confidence: 99%
“…But, as a low level of plasmatic bile acids disrupts the activity of different receptors (G protein-coupled receptor 5, TGR5, and Farnesoid X receptor, FXR), alterations of bile acid metabolism and composition have been shown to promote the development of NAFLD [ 26 , 27 ]. Obesity and diabetes have been associated with dysbiosis, which might contribute to the development and progression of NAFLD [ 28 , 29 ]. Dysbiosis induces the release of proinflammatory cytokines such as interleukins (IL-6 and IL-12) and TNF-α by macrophages and thus generates an intrahepatic inflammatory response contributing to the progression of NAFLD [ 19 , 30 ].…”
Section: Pathogenesis Of Nafldmentioning
confidence: 99%
“…A study of 92 individuals found an association of overweight/obesity with specific gut microbiota patterns when compared to those of normal weight: Bacteroidetes taxa were decreased and several Firmicutes taxa were increased ( 98 ). The Western diet is associated with decreased beneficial bacteria such as bifidobacteria and eubacteria in the human gut ( 99 ) and, in rodents, decreased Akkermansia spp., species that are associated with a number of human diseases ( 100 ). Lean mice receiving fecal transplants from mice with obesity gain weight ( 101 , 102 ) and individuals with obesity receiving transplants from lean individuals had improved metabolic disease symptoms ( 103 ).…”
Section: Meddiet and The Gut Microbiomementioning
confidence: 99%